1980
DOI: 10.1007/bf00233876
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural immunocytochemical localization of vitellogenin in the fat body of the blowfly, Calliphora vicina Rob.-Desv. (erythrocephala Meig.) by use of the unlabeled antibody-enzyme method

Abstract: The unlabeled antibody-enzyme method was used to demonstrate ultrastructurally the specific localization of vitellogenin in the fat body of Calliphora. In control flies the binding sites to vitellogenin were localized in secretory granules situated in the Golgi complex, and in larger bodies named composite secretory granules. These composite granules appear to be formed when a part of a Golgi complex containing secretory granules and a number of small vesicles become surrounded by a common membrane. Ovariectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This observation is in agreement with numerous biochemical studies (reviewed in Kunkel and Nordin 1985;Kanost et al 1990;Raikhel and Dhadialla 1992). Visualization of Vg in the fat body trophocytes has been previously performed for several insects by means of immunocytochemical techniques for fluorescent light microscopy (Tanaka and Yokizaki 1974) and electron microscopy (Couble et al 1979;Thomsen et al 1980;Mazzini et al 1989) and is particularly detailed for A. aegypti (Raikhel and Lea 1983;Raikhel 1986a, b;1987).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in agreement with numerous biochemical studies (reviewed in Kunkel and Nordin 1985;Kanost et al 1990;Raikhel and Dhadialla 1992). Visualization of Vg in the fat body trophocytes has been previously performed for several insects by means of immunocytochemical techniques for fluorescent light microscopy (Tanaka and Yokizaki 1974) and electron microscopy (Couble et al 1979;Thomsen et al 1980;Mazzini et al 1989) and is particularly detailed for A. aegypti (Raikhel and Lea 1983;Raikhel 1986a, b;1987).…”
Section: Discussionmentioning
confidence: 99%
“…The extraovaric synthesis of proteic yolk precursor, named vitellogenin, is fairly common in Arthropods. In Daphnia the most likely site of vitellogenin synthesis can be found in the fat cells, first of all for the above-mentioned functional relations between fat cells and ovaries, secondly because it has been shown that also in insects (Chen, et al, 1979;Engelmann, 1979;Thomsen et al, 1980;Zhai et al, 1984), in amphipods Meusy et al, 1983) and isopods (Picaud & Souty, 1980;Picaud, 1980;Souty & Picaud, 1981) the fat cells synthesize vitellogenin. In the stomatopods, vitellogenin is synthesized in the hepatopancreas (Ferrero, Savoini and Marzari, personal communication); however this organ is lacking in Cladocera.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed investigations in this direction will be necessary, e.g. with the antibody-enzyme method, which could help to detect vitellogenin production within Cell organelles of the oocyte (Thompson et al 1980). Giorgi et al (1976) observed that Golgi material seems to be incorporated into the surface membrane, Experientia 38 (1982), Birkhauser Verlag , CH-4010 Basel/Switzerland the oolemma.…”
mentioning
confidence: 99%